Factors Influencing Covid-19 Transmission to Patients at the Obstetrics and Gynecology Polyclinic - Ivanna Beru Brahmana; Elsye Maria Rosa (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2020)
Stay at home is one of the health protocols for the prevention of Covid-19 transmission. The prevention is obligated for pregnant women that consult the pregnancy to the doctor for Ante Natal Care. This study aims to identify the factors that influence the transmission of covid-19 in patients who come to Obstetrics & Gynecology Polyclinic. This research method is a quantitative study with a cross-sectional survey in this study amounted to 212 respondents in the Private Practitioner Primary Service Facility. Data collection was carried out by filling out the respondent's questionnaire in May-June 2020. Data analysis using SPSS software with univariate, bivariate, and multivariate methods The results of this study are based on the results of both univariate, bivariate, and multivariate analysis, it shows that the trips taken by the respondent within the last 1 month have an effect on the spread of covid-19 with a p-value of 0,000. Conclusion: Travel history 1 month before, influenced the Covid-19 incident with a p-value 0,000. Keywords: Women, Suspect Covid-19, Management Maternal, Obstetrician.